2020
DOI: 10.1177/1076029620941077
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis Recurrence and Its Predictors at Selected Tertiary Hospitals in Ethiopia: A Prospective Cohort Study

Abstract: Deep venous thrombosis (DVT) is a common clinical problem associated with substantial morbidity and mortality. Knowledge of the global burden of DVT recurrence is deficient in Africa, including Ethiopia. The objective of the study was to assess deep venous thrombosis recurrence and its predictors at selected tertiary hospitals in Ethiopia. Prospective cohort study was conducted among hospitalized DVT patients. Data were analyzed using SPSS version 21.0. To identify the independent predictors of DVT-recurrence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
5
12
1
Order By: Relevance
“…Several cohort studies showed that a previous history of VT was associated with recurrence of VT in the population younger than 70 years and a previous history of VT was independently associated with VT recurrence. 9 , 10 , 11 , 12 , 13 , 14 However, these studies generally had a short follow-up of less than 10 years, so evaluation of the association of prior VT with health and VT risk in older people could not be determined. The findings of the present study are important because they provide clinicians with quantitative information that might allow them to be aware of a future VT in people presenting for primary care or with impending provoking VT risk settings such as surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several cohort studies showed that a previous history of VT was associated with recurrence of VT in the population younger than 70 years and a previous history of VT was independently associated with VT recurrence. 9 , 10 , 11 , 12 , 13 , 14 However, these studies generally had a short follow-up of less than 10 years, so evaluation of the association of prior VT with health and VT risk in older people could not be determined. The findings of the present study are important because they provide clinicians with quantitative information that might allow them to be aware of a future VT in people presenting for primary care or with impending provoking VT risk settings such as surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients aged ≥ 65 years not only represent the majority of patients with VTE, 40 older patients are underrepresented in most previous studies examining the association between FH/PH status and recurrence. 8 9 10 11 12 13 45 50 51 Second, we used a mix of patient interviews and hospital chart review to establish FH/PH status. Patient interviews may be subject to recall bias and potentially under- or overestimate the true prevalence of FH/PH.…”
Section: Discussionmentioning
confidence: 99%
“…Deep venous thrombosis is considered the third most common cardiovascular condition following myocardial infarction and stroke, and it is a growing public health problem with 26.4% of recurrent after the patients have been diagnosed, and this results in further cost of treatment for patients and intensifies hospital's burden [ 8 ].…”
Section: Introductionmentioning
confidence: 99%